Standard specification for Seamless Copper Tube, Bright Annealed (American Society of Testing Materials, 2002)
This specification establishes the requirements for bright annealed seamless copper tube suitable for use in refrigeration, oil lines, gasoline lines, and so forth, where tube with an interior surface essentially free from scale and dirt is required.